A rights‐based proposal for managing faith‐based values and expectations of migrants at end‐of‐life illustrated by an empirical study involving South Asians in the UK. (8th June 2018) - Samanta, Jo; Samanta, Ash; Madhloom, Omar
Abstract: International migration is an important issue for many high‐income countries and is accompanied by opportunities as well as challenges. South Asians are the largest minority ethnic group in the United Kingdom, and this diaspora is reflective of the growing diversity of British society. An empirical study was performed to ascertain the faith‐based values, beliefs, views and attitudes of participants in relation to their perception of issues pertaining to end‐of‐life care. Empirical observations from this study, as well as the extant knowledge‐base from the literature, are used to support and contextualise our reflections against a socio‐legal backdrop. We argue for accommodation of faith‐based values of migrants at end‐of‐life within normative structures of receiving countries. We posit the ethically relevant principles of inclusiveness, integration and embedment, for an innovative bioethical framework as a vehicle for accommodating faith‐based values and needs of migrants at end‐of‐life. These tenets work conjunctively, as well as individually, in respect of individual care, enabling processes and procedures, and ultimately for formulating policy and strategy.